Temporal variation in environmental radioactivity and radiation exposure doses in the restricted areas around the Fukushima Daiichi Nuclear Power Plant - Liu, Mengjie; Taira, Yasuyuki; Matsuo, Masahiko; Orita, Makiko; Matsunaga, Hitomi; Kashiwazaki, Yuya; Xiao, Xu; Takamura, Noboru (Scientific reports, 2023)
Temporal variation and fluctuation in environmental contamination in Futaba town and Okuma town, the location of the Fukushima Daiichi Nuclear Power Plant (FDNPP), were evaluated based on a car-borne survey conducted from October 2021 to November 2022. Although the environmental radioactivity in the interim storage facility area (ISF) was higher than that in open areas (i.e., the evacuation order lifted areas in Futaba town and the Specific Reconstruction and Regeneration Base area [SRRB] in Okuma town), only minor temporal changes were seen in the ambient dose and detection rate of radiocesium (the proportion of radiocesium detected points per all measuring points) in those areas, respectively. These findings suggest that the observed variations may result from physical decay and environmental remediation. Resuspension caused by human activities and weather could also affect the detection rate of radiocesium. The annual external effective doses in Futaba town and Okuma town were estimated to be at a limited level (< 1 mSv/year). Nevertheless, to help ensure the safety and future prosperity of residents and communities in the affected areas around the FDNPP, long-term follow-up monitoring of temporal exposure dose levels during the recovery and reconstruction phases is extremely important.